Impact of pneumococcal vaccination on the incidence of invasive pneumococcal disease in UK PICUs. (29th September 2015) - Randle, E; McShane, P; Nolan, M; Inwald, D
Abstract : Aims: To determine the impact of pneumococcal vaccination (introduced in 2006) on the incidence of invasive pneumococcal disease (IPD) seen in UK paediatric intensive care units (PICUs). Methods: Retrospective review of cases of IPD seen in UK PICUs from 2005 to 2009, identified by primary diagnosis reported to PICANET (the national PICU Audit Network). Results: Total numbers of cases of IPD have not changed significantly since vaccination was introduced, with 64 cases in a total of 14 056 PICU admissions in 2005, 72/14 328 in 2006, 54/15 579 in 2007 and 64/16 089 in 2008 ( χ 2 p=0.18). The presentation has also remained unchanged over this period, with around 60% of cases presenting as meningitis±sepsis, 20% cases presenting as sepsis±pneumonia and 20% presenting as isolated pneumonia. Conclusions: The seven valent pneumococcal vaccine (PCV7), which covers serotypes 4, 6B, 9V, 14, 18C, 19F and 23F, was introduced in September 2006. The authors' findings suggest that despite good uptake of this vaccine, there has been no decrease in the number of cases of IPD admitted to UK PICUs. These findings are consistent with data from the Health Protection Agency, 1 which demonstrate that although vaccine serotypes have been almost eradicated since vaccination, there has been no change in the total number of cases of IPD. This is due to serotype replacement with non-vaccine serotypes. IPD is still an important cause of critical illness in children despite the pneumococcal vaccination programme.